2017
DOI: 10.1155/2017/3628127
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Resolution of Deep Vein Thromboses during Rivaroxaban Therapy

Abstract: We present the case of a patient with a deep vein thrombosis (DVT) who failed rivaroxaban therapy. Our patient initially presented with left lower extremity edema, erythema, and pain. He was subsequently started on rivaroxaban therapy for a combined treatment period of 12 months, during and after which he persisted to have evidence of a DVT. The patient's prescribed drug regimen was changed from rivaroxaban to warfarin, which demonstrated a rapid resolution of the DVTs as determined by ultrasound assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Special patient populations and characteristics that may increase risk of thromboembolic events remain areas for further investigation to confirm efficacy of these agents. [40][41][42][43][44][45] As thrombosis was a secondary endpoint of our study, patientspecific thromboembolic risk factors were not extracted, but should be priority in future studies given these endpoints occurred at a higher than expected rate.…”
Section: Discussionmentioning
confidence: 99%
“…Special patient populations and characteristics that may increase risk of thromboembolic events remain areas for further investigation to confirm efficacy of these agents. [40][41][42][43][44][45] As thrombosis was a secondary endpoint of our study, patientspecific thromboembolic risk factors were not extracted, but should be priority in future studies given these endpoints occurred at a higher than expected rate.…”
Section: Discussionmentioning
confidence: 99%
“…A thorough literature review revealed only few recent case reports on possible failure of rivaroxaban for the treatment of DVT [1,2] . Furthermore, recommendations on the ranges or cut-offs for effectiveness and efficacy have not yet been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the predictable pharmacokinetic and pharmacodynamic outcomes of DOACs, a fixed dose is administered without routine coagulation monitoring. However, data in the literature have shown variability in the anticoagulant effects of DOACs, raising concerns about their effectiveness and safety [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, multiple cases of VTE during the use of DOACs are reported in the literature [9][10][11][12]. Although the number of individual case reports is limited and clearly does not represent the majority of patients using anticoagulants, further exploration is warranted given the potential risk for the individual patient.…”
Section: Demographicsmentioning
confidence: 99%